Diplomasi Daerah Jawa Barat dalam Menghadapi Pandemi Covid-19 - Windy Dermawan; Ichsanul Amal; Gilang Nur Alam (Public Knowledge, 2025)
West Java is one of the provinces in Indonesia that has been affected by the spread of Covid-19. The West Java Provincial Government is trying to deal with the Covid-19 virus through overseas activities. This has shown the efforts of the West Java Provincial Government's efforts to overcome the medical case while trying to maintain the sustainability of the regional economy through its diplomatic activities. West Java's regional diplomatic activities in the Covid-19 era have confirmed the role of regions abroad that meet regional needs and contribute to national interests. This research aims to describe West Java's regional diplomacy in dealing with the Covid-19 pandemic, both in terms of health and economy to meet the security of West Java residents. The approach method in this research uses a qualitative method with a descriptive nature, data collection is carried out through literature studies, documentation studies and internet-based studies. The concept used in this research is Regional Diplomacy. This research found that West Java carried out its regional diplomacy to deal with Covid-19 by facilitating cooperation in improving health services, research on vaccinations to support regional health management. This research also found that both provincial actors and city and district actors in West Java to non-governmental actors such as universities carried out their regional diplomacy. This further strengthens the role of regional actors abroad to meet the needs of their regions.